The journey of Crazy Horse : a Lakota history - Marshall, Joseph, 1945- (Penguin Books, 2005)
A Lakota historian and storyteller offers a portrait of Crazy Horse, the era in which he lived, and his legacy, drawing on his own culture's oral tradition and firsthand research to capture diverse aspects of Crazy Horse's life.